Worldwide research trends on land tenure - Salmerón-Manzano, Esther; Manzano-Agugliaro, Francisco (Land Use Policy, 2023)
Land tenure issues can contribute to food insecurity, limited livelihood opportunities and consequently poverty. Lack of land tenure can cause migratory movements that can affect not only individuals and families but also communities or even entire nations. This study aims to underline the scientific and social relevance of land tenure studies by identifying research focus and trends. To this end, we analyzed all scientific publications related to land tenure from 1950 to 2020. The three most active countries in this field are the United States, the United Kingdom and Australia. The three most active countries in this field are the United States, the United Kingdom, and Australia, with the three main institutions being Wageningen University & Research, the University of Wisconsin-Madison, and the Norwegian University of Life Sciences. Three different research periods have been identified in this domain. In the period from 1950 to 1999, the main research clusters identified were related to socioeconomics and demography issues. In the second period, from 2000 to 2009, the main research clusters identified were related to specific geographical areas and land rights issues, with an emphasis on countries in Africa or South America. In the third period, from 2010 to 2020, the main research clusters identified were related to environmental aspects. It has been found that land tenure studies have always been linked to what subsequently became the sustainable development goals, especially those related to the elimination of poverty and hunger in the first period, economic growth and reducing inequalities in the second period, and climate change in the third period. From a geographical point of view, the first two periods were characterized by terms related to continents such as Africa, Asia, or Latin America, with Africa being the most frequently used term in the first two periods. In the third period, studies on specific countries stood out, especially those related to China and Mexico.
Keywords: agriculture; bibliometric; deforestation; developing countries; environmental accounting; land reform; land use; Sustainability; Sustainable Development Goals; Scopus; JCR